2021
DOI: 10.3390/molecules26061812
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Hazomalania voyronii Essential Oil Nanoemulsion for the Eco-Friendly Management of Tribolium confusum, Tribolium castaneum and Tenebrio molitor Larvae and Adults on Stored Wheat

Abstract: Most insecticides commonly used in storage facilities are synthetic, an issue that generates concerns about food safety and public health. Therefore, the development of eco-friendly pest management tools is urgently needed. In the present study, a 6% (w/w) Hazomalania voyronii essential oil-based nanoemulsion (HvNE) was developed and evaluated for managing Tribolium confusum, T. castaneum, and Tenebrio molitor, as an eco-friendly wheat protectant. Larval and adult mortality was evaluated after 4, 8, and 16 h, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Recently, Kavallieratos et al [ 224 ] tested an essential botanical oil-based nanoemulsion (HvNE) (isolated from Hazomalania voyronii (Jum.) (Hernandiaceae)) applied as a wheat grain protectant against three storage Coleoptera species.…”
Section: Delivery Of Insecticides As Liquids (Admixtures Liquid Baits Aerosols Sprays Etc)mentioning
confidence: 99%
“…Recently, Kavallieratos et al [ 224 ] tested an essential botanical oil-based nanoemulsion (HvNE) (isolated from Hazomalania voyronii (Jum.) (Hernandiaceae)) applied as a wheat grain protectant against three storage Coleoptera species.…”
Section: Delivery Of Insecticides As Liquids (Admixtures Liquid Baits Aerosols Sprays Etc)mentioning
confidence: 99%
“…The founding individuals of T. castaneum and T. granarium have been collected from Greek storage facilities since 2003 and 2014, respectively. The selected insect individuals of both species and developmental stages, as well as the conditions they were cultured in, were adapted from previous studies [40,59].…”
Section: Insect Speciesmentioning
confidence: 99%
“…Essential oils have been studied in relation to their fumigant toxicity [30][31][32] and their contact toxicity [33][34][35], but only recently has there been a focus on novel application methods of EOs [36,37]. This research interest became fruitful by providing a solid methodological approach for the application of volatile compounds as stored grain coatings in the form of nanoemulsions (NE) [38][39][40][41]. Microemulsions (ME), on the other hand, are kinetically stable, oily droplets in water, with a Surfactant-to-Oil Ratio (SOR) usually higher than 2 [42].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1. Gas chromatogram profiles of peak retention of components of oregano essential oil: α-thujene (1), α-pinene (2), camphene (3), β-pinene (4), β-myrcene (5), α-phellandrene (6), α-terpinene (7), p-cymene (8), eucalyptol (9), γ-terpinene (10), cis-sabinene hydrate (11), terpinolene (12), linalool (13), camphor (14), borneol (15), terpinen-4-ol ( 16), α-terpineol (17), thymol methyl ether (18), carvacrol methyl ether (19), cuminaldehyde (20), thymol (21), carvacrol (22), aromandrene (23), β-bisabolene (24), and caryophyllene oxide (25).…”
Section: Chemical Oeo Characterizationmentioning
confidence: 99%
“…The biological activity on insects caused by EOs varies according to plant species, and their efficacy has been demonstrated in coleopteran stored product pests [12,15,23]. Previous studies showed that Cymbopogon citratus essential oil is lethal to Ulomoides dermestoides Fairmaire (Tenebrionidae) [16], Hazomalania voyronii essential oil to Tribolium confusum (du Val) (Tenebrionidae) [24], and Zingiber pupureum essential oil to Lasioderma serricone Fabricius (Anobiidae) [25], favoring an effective approach toward Integrated Resistance Management (IRM). In this context, EOs from Amarydillaceae [26], Annonaceae [20], Lauraceae [27], Meliaceae [28], and Poaceae [29] are the most promising for causing toxic effects in insects.…”
Section: Introductionmentioning
confidence: 99%